Dancing Archives - Archive Dances : Exploring Dance Histories at the Radcliffe College Archives - Hecht, Thom (TanzScripte ;, 2013)
This book presents the first in-depth archival exploration of a lost history of dance as an extracurricular activity at Radcliffe College, the women's liberal arts college of Harvard University, during the first half of twentieth century. Using archival story-ing, an innovative methodology that brings the researcher's lived experience at the Radcliffe College Archives into the historical discourse, three archive stories were created. These vivid narratives thrive in the researcher's personal encounters with the surroundings of the archive and the interpretation and reading of what is to be found giving profound insights into what it means to walk in the footsteps of Radcliffe dance history.